Pancreatic Cancer (Springer New York, 2018)
In organizing the second edition of this renowned Handbook, Dr. Neoptolemos and his co-editors have produced and updated a revised edition to the distinguished Major Reference Work devoted to pancreatic cancer. Like its preceding edition, the second edition continues to have a widespread appeal among clinicians, pathologists and basic scientists, who are now struggling to understand this complex and rapidly expanding field. Because of the recent and vast growth in both the clinical and scientific research being done in pancreatic cancer, (there is currently an unprecedented investment by academia and industry in this field), each research's knowledge of other specialty areas outside his or her own is often quite limited. The aim of the new edition is to place the tangible advances, including new developments in surgical approaches with regards to resection techniques, the state of laparoscopic approaches, the growing impact of surgical approaches in the management of recurrent pancreatic cancer, controversies in the management of IMPN as the precursor lesion for PDAC and others - readily at hand. The second edition focuses on advances that will not become dated, and the editors have chosen authors, who are the very best in each area.